Relationship Between Family Support with Anxiety of Death Among Elderly - Rodiana Kurniasih; Siti Nurjanah (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Elderly is the final stage of development in the human life cycle, the experience changes in physically, psychologically and socially so that it will affect the overall function and ability of the body.  With such conditions can cause various problems in the elderly as anxiety, especially anxiety about death. The aim of the study is to find out the relationship between family support with anxiety of death among elderly in Desa Kalisari Kecamatan Cilongok. This research is a correlation study. The population in this study were 42 elderly. With a sample size of 39 elderly people who were taken randomly using a Random Number Generator. The data collection technique used a questionnaire. This study used the Spearman rank test, obtained a correlation coefficient of 0.442 with a significance value (p-value) of 0.008, means that there is a relationship between family support and anxiety of death among the elderly in Kalisari Village, Cilongok District. Researchers suggest that the elderly don’t be too anxious, the elderly can draw closer to or deepen the knowledge of religion to help reduce anxiety in themselves.